2016
DOI: 10.1097/md.0000000000004731
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calcineurin inhibitors in the treatment of IgA nephropathy

Abstract: Background:Immunoglobin A nephropathy (IgAN), the most prevalent form of primary glomerulonephritis, represents the leading cause of kidney failure among East Asian populations. Immunosuppressive treatment regimen, except for a 6-month trial of corticosteroids, has not been approved by the KDIGO guideline yet. Specific and effective treatment is still lacking. We decided to evaluate the efficacy and safety of the calcineurin inhibitors (CNIs) in the treatment of IgAN.Methods:Database from the Cochrane library,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…Our results are similar to those of a previous study showing that patients with IgAN may experience significant improvement in proteinuria and hypoalbuminemia during TAC treatment. 43 Moreover, this meta-analysis concluded that there is no significant difference in the relative risk of adverse events at the end of treatment or during follow-up. IgAN patients who achieved remission had far better outcomes than those who did not.…”
Section: Discussionmentioning
confidence: 93%
“…Our results are similar to those of a previous study showing that patients with IgAN may experience significant improvement in proteinuria and hypoalbuminemia during TAC treatment. 43 Moreover, this meta-analysis concluded that there is no significant difference in the relative risk of adverse events at the end of treatment or during follow-up. IgAN patients who achieved remission had far better outcomes than those who did not.…”
Section: Discussionmentioning
confidence: 93%
“…It is a relatively benign disease, however, the long term prognosis should not be considered mild, because, after 20 years of disease progression, 20–50% of the patients reach end stage renal disease 3 6 . A number of immunosuppressive agents have been used for treatment of IgAN, including calcineurin inhibitors 7 , 8 , azathioprine 9 , mycophenolate mofetil 10 , 11 , cyclophosphamide 11 , 12 , leflunomide 13 , 14 , corticosteroids 12 , 15 17 , etc. Many studies have only compared two treatment regimens for a relatively small sample size.…”
Section: Introductionmentioning
confidence: 99%
“…However, no recommendation was made for patients with eGFR < 45 ml/min/1.73m 2 . Given that some studies supported the use of steroids or immunosuppressants [7][8][9] for these patients, which is also widely applied clinically, thus we conducted this study to explore whether corticosteroids or immunosuppressant therapies could improve the renal outcome of patients with advanced IgAN (eGFR < 45 mL/min/1.73 m 2 and mean proteinuria > 1 g/24h).…”
Section: Introductionmentioning
confidence: 99%